In Vitro Interactions Between Bacteriophages and Antibacterial Agents of Various Classes Against Multidrug-Resistant Metallo-β-Lactamase-Producing Pseudomonas aeruginosa Clinical Isolates - Paschalis Paranos; Sophia Vourli; Spyros Pournaras; Joseph Meletiadis (Pharmaceuticals)
Background: Combination therapy with antibiotics and phages has been suggested to increase the antibacterial activity of both antibiotics and phages. We tested the in vitro activity of five antibiotics belonging to different classes in combination with lytic bacteriophages against multidrug-resistant metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa isolates. Material/Methods: A total of 10 non-repetitive well-characterized MBL-producing P. aeruginosa isolates (5 NDM, 5 VIM) co-resistant to aminoglycosides and quinolones were used. Phage–antibiotic interactions were assessed using an ISO-20776-based broth microdilution checkerboard assay in 96-well microtitration plates. Two-fold dilutions of colistin (8–0.125 mg/L), ciprofloxacin, meropenem, aztreonam, and amikacin (256–4 mg/L) were combined with ten-fold dilutions of five different phages (5 × 109–5 × 100 PFU/mL) belonging to Pakpunavirus, Phikzvirus, Pbunavirus, and Phikmvvirus genus. Plates were incubated at 35 ± 2 °C for 24 h, and the minimum inhibitory concentration of antibiotics (MICA) and phages (MICP) were determined as the lowest drug and phage concentration, resulting in <10% growth based on photometric reading at 550 nm. Interactions were assessed based on the fractional inhibitory concentration index (FICi) of three independent replicates and clinical relevance based on the reversal of phenotypic resistance. The statistical significance of each drug alone and in combination with phages was assessed using GraphPad Prism 8.0. Results: Synergistic and additive interactions were found for 60–80% of isolates for all drugs. FICis were statistically significantly lower than 0.5 for colistin (p = 0.005), ciprofloxacin (p = 0.02), meropenem (p = 0.003), and amikacin (p = 0.002). Interactions were found at clinically achievable concentrations for colistin, meropenem, and amikacin, and a reversal of phenotypic resistance was observed for most strains (63–64%) for amikacin and meropenem. Antagonism was found for few isolates with all antibiotics tested. Phage vB_PaerM_AttikonH10 and vB_PaerP_AttikonH4 belonging to Phikzvirus and Phikmvvirus genus, respectively, showed either synergistic (FICi ≤ 0.35) or additive effects with most antibiotics tested. Conclusions: Synergy was observed for most drugs and phages with amikacin, showing strong synergy and reversal of phenotypic resistance against most isolates. Taking into account the wide utility of jumbo phages obtained, the findings of vB_PaerM_AttikonH10 in combination with different classes of antibiotics can enhance the activity of currently ineffective antibiotics against MBL-producing P. aeruginosa isolates.